2008
DOI: 10.1111/j.1420-9101.2008.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the extent of genome‐wide intralocus sexual conflict via experimentally enforced gender‐limited selection

Abstract: Intralocus sexual conflict, which occurs when a trait is selected in opposite directions in the two sexes, is a taxonomically widespread phenomenon. The strongest genetic evidence for a gender load due to intralocus sexual conflict comes from the Drosophila melanogaster laboratory model system, in which a negative genetic correlation between male and female lifetime fitness has been observed. Here, using a D. melanogaster model system, we utilize a novel modification of the ‘middle class neighbourhood’ design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 34 publications
(64 reference statements)
5
75
0
Order By: Relevance
“…Anecdotal evidence exists for turnover of sex determination due to sexual conflict in cichlid (Roberts et al 2009) and stickleback fish (Kitano et al 2009). The evidence for considerable sex differences in gene expression in animals (Kopp et al 2003;Morrow et al 2008;Mainguy et al 2009;Mank 2009a) suggests that sexual antagonism is possible at many genes. However, several other models for changes in GSD exist (Bull 1983;Vuilleumier et al 2007;Kozielska et al 2010), and it is difficult to test which model best fits the observed patterns.…”
Section: Lessons From Genetic Mapping Of Sex-determining Locimentioning
confidence: 99%
“…Anecdotal evidence exists for turnover of sex determination due to sexual conflict in cichlid (Roberts et al 2009) and stickleback fish (Kitano et al 2009). The evidence for considerable sex differences in gene expression in animals (Kopp et al 2003;Morrow et al 2008;Mainguy et al 2009;Mank 2009a) suggests that sexual antagonism is possible at many genes. However, several other models for changes in GSD exist (Bull 1983;Vuilleumier et al 2007;Kozielska et al 2010), and it is difficult to test which model best fits the observed patterns.…”
Section: Lessons From Genetic Mapping Of Sex-determining Locimentioning
confidence: 99%
“…There is also evidence of phenotypic plasticity in sperm morphology. Thus, studies have shown that sperm size can be adjusted under different social scenarios [33][34][35]. The influence of the social environment on the ovum phenotype has not before been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, numerous studies have tested the efficacy of sexual selection in aiding adaptation by modifying the strength of sexual selection to study evolutionary responses from standing genetic variation (e.g., Holland and Rice 1999;Holland 2002;Martin and Hosken 2003;Rundle et al 2006;Fricke and Arnqvist 2007;Morrow et al 2008;Jarzebowska and Radwan 2010;Maklakov et al 2010;Plesnar-Bielak et al 2012;Chenoweth et al 2015;Lumley et al 2015) or purging naturally accumulated (e.g., Radwan et al 2004;Rundle et al 2006;Mallet et al 2011;McGuigan et al 2011;Sharp and Agrawal 2013) or artificially induced/introduced deleterious mutations (e.g., Radwan 2004;Sharp and Agrawal 2008;Hollis and Houle 2011;Plesnar et al 2011;Arbuthnott and Rundle 2012;Clark et al 2012;Almbro and Simmons 2013;Power and Holman 2015;Grieshop et al 2016). The results of these studies have been inconsistent, which allows several insights.…”
Section: Introductionmentioning
confidence: 99%